2013
DOI: 10.1080/00958972.2013.767450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lanthanide contraction on the Ln/Sb/Se/dien system: solvothermal syntheses and characterizations of lanthanide(III)-selenidoantimonate complexes with diethylenetriamine as a co-ligand

Abstract: 2013) Effect of lanthanide contraction on the Ln/Sb/Se/dien system: solvothermal syntheses and characterizations of lanthanide(III)-selenidoantimonate complexes with diethylenetriamine as a coligand, Journal of Coordination Chemistry, 66:4, 650-661,The ternary system Ln/Sb/Se was investigated in a diethylenetriamine (dien) solvent under solvothermal conditions and two types of neutral lanthanide(III)-selenidoantimonate complexes [Ln(dien) 2 (μ-η 1 ,η 2 -SbSe 4 )] n (Ln = Pr(1), Nd (2)) and [Ln(dien) 2 (η 2 -Sb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The Table S6). The NÁÁÁSe separations and N-HÁÁÁSe angles are in agreement with reported values observed in Ln tetraselenidoantimonate containing amino coligands [41][42][43][44]48]. The layers are further connected through interlayer N-HÁÁÁSe interactions to form a 3-D H-bonding network (Fig.…”
Section: Crystal Structures Of 1a and 1bsupporting
confidence: 90%
See 3 more Smart Citations
“…The Table S6). The NÁÁÁSe separations and N-HÁÁÁSe angles are in agreement with reported values observed in Ln tetraselenidoantimonate containing amino coligands [41][42][43][44]48]. The layers are further connected through interlayer N-HÁÁÁSe interactions to form a 3-D H-bonding network (Fig.…”
Section: Crystal Structures Of 1a and 1bsupporting
confidence: 90%
“…ions and chalcogenidoantimonate anions via TM-S or TM-Se bond, the weak interactions between lanthanide (Ln) ions and chalcogenidoantimonate anions make the synthesis of ternary Ln-chalcogenidoantimonates a challenging task. However, our work has demonstrated that the chalcogenidoantimonate anions [SbS 4 ] 3-and [SbSe 4 ] 3-can coordinate to Ln(III) centers using coordinative amines as co-ligands, and a number of Ln-chalcogenidoantimonates have been solvothermally prepared in en, dien, and trien solvents [39][40][41][42][43][44]. Unlike the TM n?…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A search from the Cambridge Crystallographic Data Centre (CCDC) shows that there are dozens of complexes containing samarium [36][37][38][39][40]. However, among these complexes, only several are samarium-containing complex with bipy [41][42][43][44][45].…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%